The effect of leaflet-based education and simulation of first-aid in accidents (P3K) on the knowledge and skills of tourism workers in Indonesia - Adelia Permatasari; Anita Sulistyorini; Supriyadi Supriyadi; Nurnaningsih Herya Ulfah (Public Health and Occupational Safety Journal)
Background: Law Number 1 of 1970 concerning Occupational Safety requires all sectors, including tourism, to implement Occupational Safety and Health (K3). Taman Dolan Batu City, as a tourist destination, has a risk of work accidents, so it needs mitigation efforts through First Aid for Accidents (P3K).